LOKAKARYA KOMUNITAS BELAJAR 1 PROGRAM SEKOLAH PENGGERAK (PSP) ANGKATAN 3 KABUPATEN SIMALUNGUN - Darmawati, Darmawati; Parinduri, Luthfi; Parinduri, Muhammad Ali Hadidie (Universitas Islam Sumatear Utara, 2024)
The 21st century, teachers as educators must be responsive to change. One crucial aspect for an educator is how a teacher responds to changes through small innovations in their workplace..The Community Learning Workshop 1 of the School Empowerment Program (PSP) Generation 3 in Simalungun Regency convened at SDN 091440 Manik Hataran, Sidamanik District, Simalungun Regency, engaging 20 teachers. This workshop served multiple objectives: educating attendees on pertinent learning, knowledge, and teaching practices; fostering collaborative support among practitioners; particularly assisting novice members to seamlessly integrate into the community; and mentoring them in their tasks. Furthermore, it encouraged skill dissemination and growth among members through discussions and practical teaching practices. The workshop exemplified a concerted effort to enhance educational practices in Simalungun Regency, emphasizing the importance of collaborative learning and community support in advancing education.